(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article is devoted to the theoretical study of the functions of civil law. The functions of civil law are the impact of civil law norms in certain directions on property relations, as well as on related or unrelated personal non–property relations. The author considers the main functions of civil law to be: regulatory, protective, human rights, educational, compensatory, restorative, punitive functions. Attention is drawn to the fact that functions can be discussed not only at the general theoretical level, but also at the level of a specific branch of law, legal institution or legal norm.